Legacy effect on neuropsychological function in HIV-infected men on combination antiretroviral therapy. (1st January 2022) - Qu, Yang; Weinstein, Andrea; Wang, Zheng; Cheng, Yu; Kingsley, Lawrence; Levine, Andrew; Martin, Eileen; Munro, Cynthia; Ragin, Ann B.; Rubin, Leah H.; Sacktor, Ned W.; Seaberg, Eric C.; et al.
Abstract : Objective: To determine whether combination antiretroviral therapy (cART) initiation alters the trajectory of cognitive performance in HIV+ men, and whether cognition prior to cART predicts postcART function. Design: Longitudinal cohort study. Multicenter AIDS Cohort Study. Methods: From an initial set of 3701 men with complete neuropsychological data, men with HIV infection were initially matched with men without infection on cognitive status, race, age, and timeline (T0 defined as cART initiation). Propensity score matching was then used to match pairs on depressive symptoms at T0, education, T0 cognitive scores, and recruitment cohort. There were 506 matched pairs of infected and uninfected men in the final analysis. Mixed effect models were constructed to analyze the trajectories of cognitive functions and to test the effect of cART and HIV on cognitive functions over time. Results: Performance in each cognitive domain did not change following the initiation of cART among HIV-infected men with prior impairment and was comparable to the performance of their matched uninfected men. However, among the infected men who were unimpaired prior to cART, motor function declined significantly faster than it did for uninfected controls. Conclusions: Cognitive dysfunction is persistent in HIV-infected men and cART does not alter the trajectory of cognitive decline in men who were impaired prior to effective therapy. This suggests that current cognitive impairment in HIV+ men results from a legacy effect, and from factors other than the HIV itself. Furthermore, motor skills may be uniquely vulnerable to the virus, cART, or age-related co-morbidities. Abstract : Supplemental Digital Content is available in the text